Substrate preparation for optimized growth of vertically aligned carbon nanofibers - Xiaohui, Cao (My University, 2010)
In order to explore the optimal growth condition of carbon nanofibers on patterned metal on isolating substrate, we employ colloidal lithography to realize the mass production of test chips. We achieve these catalyst dots with short-range ordering, which are semi-quantitatively characterized by SEM and a radial distribution function. In addition, we explore the relation between the deposition conditions and the resistivities of TiN films coming out of our sputtering machine.
Keywords: Materialvetenskap; Nanovetenskap och nanoteknik; Elektrofysik; Övrig teknisk materialvetenskap; Materials Science; Nanoscience & Nanotechnology; Electrophysics; Other materials science